Perspective on the Multiple Pathways to Changing Brain States - Tantirigama, Malinda L. S.; Zolnik, Timothy; Judkewitz, Benjamin; Larkum, Matthew E.; Sachdev, Robert N. S. (Frontiers in Systems Neuroscience, 2020)
In this review we highlight several disparate ideas that are linked to changes in brain state (i.e. sleep to arousal, Down to Up, synchronized to de-synchronized). In any discussion of brain state, we propose that the cortical pyramidal neuron has a central position. EEG recordings, which typically assess brain state, predominantly reflects the activity of cortical pyramidal neurons. This means that the dominant rhythmic activity that characterize a particular brain state has to ultimately manifest globally across the pyramidal neuron population. During state transitions, it is the long-range connectivity of these neurons that broadcast the resultant changes in activity to many subcortical targets. Structures like the thalamus, brainstem/hypothalamic neuromodulatory systems and respiratory systems can also strongly influence brain state, and for many decades we have been uncovering bidirectional pathways that link these structures to state changes in the cerebral cortex. More recently, movement and active behaviors have emerged as powerful drivers of state changes. Each of these systems involve different circuits distributed across the brain. Yet, for a system-wide change in brain state there must be a collaboration between these circuits that reflects and perhaps triggers the transition between brain states. As we expand our understanding of how brain state changes, our current challenge is to understand how these diverse set of circuits and pathways interact to produce the changes observed in cortical pyramidal neurons.